Use of social media to enhance personal learning environment in learning of statistics - Au Yong, Hui Nee (2015)
A Personal Learning Environment (PLE) has been discussed from the past few years as PLE empowers students to take charge of their own learning to match their personal learning style and pace. Many students in tertiary education face difficulties in learning statistics and mathematical skills because of its complexity, lack of self motivations and learning supports. The objective of this study is to verify on how online learning tools such as social media can serve as platforms for PLE integrating both formal and informal learning and fostering self-regulated learning for statistics learners. A survey questionnaire was tested among students from a private university. Likert-scale type format and open-ended question were used. Findings from this study show that most learners are accessing internet. However, its use for learning was still low and required further improvement. Spending more time in social network was found correlated with receiving a stronger intrinsic motivation. Instructors should use social media integrated in the LMS with interesting course content. Results from this pilot study have contributed to the questionnaire for future full implementation.